2012
DOI: 10.1371/journal.pone.0040586
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Protein A Plays a Critical Role in Mediating Bone Destruction and Bone Loss in Osteomyelitis

Abstract: Staphylococcus aureus is the most frequent causative organism of osteomyelitis. It is characterised by widespread bone loss and bone destruction. Previously we demonstrated that S. aureus protein A (SpA) is capable of binding to tumour necrosis factor receptor-1 expressed on pre-osteoblastic cells, which results in signal generation that leads to cell apoptosis resulting in bone loss. In the current report we demonstrate that upon S. aureus binding to os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
128
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(133 citation statements)
references
References 46 publications
3
128
0
2
Order By: Relevance
“…*, statistical significance compared to the results observed with the isogenic parent strain in both cell types. tracellular forms (41,42) and was previously shown to bind to preosteoblastic cells via tumor necrosis factor alpha receptor 1, resulting in apoptosis and, ultimately, bone loss (43). Thus, protein A was present in increased amounts in UAMS-1 relative to the amounts in LAC (Spa in Table 1) and could have contributed to the virulence of UAMS-1, and elimination of PSM production in UAMS-1 had comparatively little impact in this model.…”
Section: Figmentioning
confidence: 80%
“…*, statistical significance compared to the results observed with the isogenic parent strain in both cell types. tracellular forms (41,42) and was previously shown to bind to preosteoblastic cells via tumor necrosis factor alpha receptor 1, resulting in apoptosis and, ultimately, bone loss (43). Thus, protein A was present in increased amounts in UAMS-1 relative to the amounts in LAC (Spa in Table 1) and could have contributed to the virulence of UAMS-1, and elimination of PSM production in UAMS-1 had comparatively little impact in this model.…”
Section: Figmentioning
confidence: 80%
“…SpA can promote binding to osteoblasts, which results in activation of osteoclasts and inhibition of osteoblast proliferation and mineralization. In addition, SpA binding to osteoblasts induces apoptosis via caspase 6 activation (Claro et al, 2011;Widaa et al, 2012). These effects are believed to contribute to the bone loss observed in osteomyeltitis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we demonstrated that SpA binding to osteoblasts generates a signal that induces osteoblast apoptosis. Deletion of SpA from S. aureus prevented these events from occurring, suggesting that the S. aureus SpA-osteoblast interaction is a critical event in upsetting normal bone remodelling (Claro et al, 2011;Widaa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Bone remodeling is necessary for skeletal growth and the maintenance of bone structure, and it depends on the balance between bone resorption and formation [3]. The resorption of bone by osteoclasts is followed by new bone formation by osteoblasts in a complex cascade of events involving several factors [4]. The maturation of osteoblasts is characterized by the expression of alkaline phosphatase (ALP), which is important for bone matrix deposition and mineralization, whereas differentiated mature osteoblasts produce osteocalcin and osteopontin to regulate matrix mineralization [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It is an opportunistic pathogen capable of producing a large number of virulence factors that mediate its attachment to host cells. The infection of bone tissue alters the bone remodeling process regulated by osteoblasts and osteoclasts [4,9]. S. aureus is internalized by phagocytic vesicles in osteoblasts, protecting the bacteria from immune or antibiotic attack and leading to osteoblast apoptosis and the prevention of new bone formation [10,11].…”
Section: Introductionmentioning
confidence: 99%